The Influence of Brand Image and Sustainability Awareness on Customer Loyalty at Miniso Medan Mall: Pengaruh Citra Merek dan Kesadaran Keberlanjutan terhadap Loyalitas Pelanggan Miniso Medan Mall - Cindy; Hommy Dorthy Ellyany Sinaga; Ngiw Aman Harja (Sekolah Tinggi Ilmu Ekonomi Eka Prasetya, 2025)
This study aims to analyze the Influence of Brand Image and Sustainability Awareness on Customer Loyalty at Miniso Medan Mall. The research method used is a quantitative approach by distributing questionnaires to 91 respondents who are customers of Miniso Medan Mall. Data were analyzed using validity tests, reliability tests, multiple linear regression, t-tests, F-tests, and the coefficient of determination with the help of SPSS Version 27. The results showed that Brand Image had a positive and significant effect on Customer Loyalty, while Sustainability Awareness had a positive but insignificant effect on customer loyalty. Simultaneously, both variables have a significant effect on customer loyalty with a coefficient of determination of 62.9%. This confirms that customer loyalty toward Miniso Medan Mall is more strongly influenced by Brand Image perceptions than by Sustainability Awareness. The findings of this study have practical implications for Miniso to continue strengthening product quality, design, and shopping experience, while maintaining its commitment to Sustainability Awareness as a long-term strategy in facing modern retail competition.